Analisis Perencanaan Sumber Daya Manusia (SDM) dalam Peningkatan Mutu Pendidikan di MIS Al-Washliyah Greahan - Tengku Darmansah; Nur Aini; Ainun Hidayasha; Audia Amanda Br Tarigan; Affiq Faeyza; Sri Solihatun (Universitas Palan, 2025)
Human resources are the most important asset in an organization/business, especially in an educational institution, so they are very important. It is important that existing human resources can be planned as well as possible to achieve the goals of the organization/institution. Careful human resource planning will ensure smooth operations. Yes or no, this is the operational process of an organization/institution. There are many effective and efficient human resource planning models, but effective human resource planning and effective intentions are sometimes not realized optimally, only limited to imagination and desire. just a hope. Therefore, this research was conducted to analyze human resource planning and find solutions to problems that influence HR planning at Mis Al-Washliyah Greahan. The research method used by researchers in this research is a qualitative approach with descriptive methods using interview techniques, observation and document study. After the data is collected, classify, edit and present the data based on each data type. Before data is collected, it is first analyzed and checked for validity. The research results show that human resource planning is carried out through programs, activities, planning stages, including quality indicators or goals to be achieved in a process of improving the quality of education. This form of planning includes resource management which includes developing human resources, developing the learning process and increasing the capacity of human resources to improve the quality of education.